2017
DOI: 10.3390/app7111202
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Horizontal and Vertical Interchannel Decorrelation

Abstract: Featured Application: 3D audio mixing and upmixing; creative sound design. Abstract:The perceptual effects of interchannel decorrelation on perceived image spread have been investigated subjectively in both horizontal and vertical stereophonic reproductions, looking specifically at the frequency dependency of decorrelation. Fourteen and thirteen subjects graded the horizontal and vertical image spreads of a pink noise sample, respectively. The pink noise signal had been decorrelated by a complementary comb-fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Commercial 3D audio formats often see the inclusion of height-channel loudspeakers positioned above a mainlayer of loudspeakers-examples of such systems include Auro-3D [1], Dolby Atmos [2], and DTS:X [3]. Given the upward extension of the sound field from established twodimensional (2D) formats (e.g., 5.1 and 7.1 surround), it is necessary to conduct fundamental investigations into the perception of interchannel signal relationships in the vertical domain.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial 3D audio formats often see the inclusion of height-channel loudspeakers positioned above a mainlayer of loudspeakers-examples of such systems include Auro-3D [1], Dolby Atmos [2], and DTS:X [3]. Given the upward extension of the sound field from established twodimensional (2D) formats (e.g., 5.1 and 7.1 surround), it is necessary to conduct fundamental investigations into the perception of interchannel signal relationships in the vertical domain.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an inherent vertical spread may have occurred due to the different frequencies (melodic parts) being perceived from different heights, i.e., the pitch-height effect [18]. This hypothesis has previously been suggested by the authors in earlier studies, where a potential pitch-height effect was observed when vertically decorrelating band-limited pink noise at 0 • azimuth [8], [19], however, additional investigations are required to assess the hypothesis further.…”
Section: A Sound Source Dependencymentioning
confidence: 93%
“…Decorrelation is also frequency dependent [121]. Since low-frequency decorrelation has been reported to be important for LEV [122], various decorrelation methods have been proposed [118,123,124]. Furthermore, decorrelation of vertically oriented signals has been found to have a minimal, or no, effect on the vertical spread of virtual sources, depending on source frequency [124,125].…”
Section: Perceptually Motivated Approachesmentioning
confidence: 99%